ANALISIS RIBA PADA PRODUK ASURANSI SYARIAH - Rizqy, JIHAN JUWITA RIZQY (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
The agreement in Islamic insurance is designed to be free from usury. The premiums paid by participants are invested according to Islamic law, and the profits are considered the result of mudharabah (business cooperation), not usury. The study found that public awareness and interest in Islamic insurance is increasing as Islamic financial literacy improves. In conclusion, it is important to understand and apply sharia principles in financial products to comply with Islamic teachings and the needs of the people. This research uses a descriptive-qualitative method with a rationalistic approach, which combines in-depth analysis with literature review from various sources. The results show that Islamic insurance seeks to avoid usury, focusing on mutual aid and cooperation for good, as per the teachings of the Quran. Islamic insurance companies emphasize social benefits more than economic profits.